1998
DOI: 10.1021/jp980121+
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Crystal Structure of Acetylacetone at 210 and 110 K:  Is the Crystal Disorder Static or Dynamic?

Abstract: The molecular and crystal structure of acetylacetone (AA) was studied at 210 and 110 K in order to reveal the nature of the hydrogen bond and possible crystal disorder. The single crystal was grown by an in situ crystallization from the melt using an IR laser beam producing a molten zone in a Lindeman capillary. At both temperatures the crystals are orthorhombic (space group Pnma, Z = 4) with molecules having a crystallographic mirror plane perpendicular to the mean molecular plane. The intramolecular hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 34 publications
8
64
2
Order By: Relevance
“…The O ¥¥¥ O distance in 1a,c and in 1b are 2.546 and 4.185 ä, respectively. The first value agrees with both experimental results and elaborate calculations: 2.381 [36] and 2.512 ä [37] by electron diffraction; 2.547 ä by X-ray diffraction at 110 K [31], and 2.535 ä by X-ray diffraction of DPHEAD [32]; and 2.549 or 2.548 ä by MP2/D95 ** [38] or MP2(FC)/6-311 G(2d,2p) [39] calculations, respectively. For 1b, Karle et al [36] experimentally determined the O ¥¥¥ O distance as 2.767 ä, the calculated values [38] being 4.046 and 3.559 ä for the more-and the less stable forms, respectively.…”
Section: Computational Experimentssupporting
confidence: 86%
See 2 more Smart Citations
“…The O ¥¥¥ O distance in 1a,c and in 1b are 2.546 and 4.185 ä, respectively. The first value agrees with both experimental results and elaborate calculations: 2.381 [36] and 2.512 ä [37] by electron diffraction; 2.547 ä by X-ray diffraction at 110 K [31], and 2.535 ä by X-ray diffraction of DPHEAD [32]; and 2.549 or 2.548 ä by MP2/D95 ** [38] or MP2(FC)/6-311 G(2d,2p) [39] calculations, respectively. For 1b, Karle et al [36] experimentally determined the O ¥¥¥ O distance as 2.767 ä, the calculated values [38] being 4.046 and 3.559 ä for the more-and the less stable forms, respectively.…”
Section: Computational Experimentssupporting
confidence: 86%
“…Besides, Boese et al investigated the structure of 1 at low temperatures (110 and 210 K; CSD entries LIWPIQ and LIWPIQ01, resp.). At these temperatures, 1 exists as a dynamic mixture of 1a and 1c (double-well potential) [31]. We selected the DPHEAD structure (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunneling effects from the three large-amplitude motions splits each vibrational level into several sublevels, and complicates the tunneling splitting patterns of the molecule. Extensive experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and theoretical [16][17][18][19][20][21][22][23][24] studies for enolic acetylacetone have been presented in the literature, but the studies of the tunneling splitting patterns are still lacking. Since the tunneling splitting patterns depend on the molecular symmetry and intramolecular motions of a molecule, the equilibrium structure and intramolecular motions must be determined before starting this work.…”
Section: Introductionmentioning
confidence: 99%
“…4 These interactions are characterized by a lower barrier to proton transfer and a high energy of the hydrogen bond, which is stabilized through π electron density delocalization in the hydro gen bonded six membered ring. It was suggested that the O-H...O bond strength, for which the interatomic O...O distance serves as an estimate, depends on the nature of the substituents at the carbon atoms of the keto enol ring because these distances in structurally similar acetyl acetone, 4 benzoylacetone, 5 and tetraacetylethane 3 differ in value (2.547(1), 2.502(4), and 2.450(1) Å, respectively). However, no such differences were observed in the iso lated molecules of these compounds.…”
mentioning
confidence: 99%